Accelerated fatigue testing of dentin-composite bond with continuously increasing load. Issue 6 (June 2017) - Li, Kai; Guo, Jiawen; Li, Yuping; Heo, Young Cheul; Chen, Jihua; Xin, Haitao; Fok, Alex
Highlights: Accelerated fatigue with a continuously increasing load was used to test dentin-composite bond. Data were analyzed using a probabilistic model based on the Weakest-Link Theory. All experimental data could be well fitted with a 2-parameter Weibull function. The method allows fatigue parameters to be determined more efficiently. The model can be used to assess composite systems in a more clinically relevant manner. Abstract: Objectives: The aim of this study was to evaluate an accelerated fatigue test method that used a continuously increasing load for testing the dentin-composite bond strength. Methods: Dentin-composite disks (ϕ5 mm × 2 mm) made from bovine incisor roots were subjected to cyclic diametral compression with a continuously increasingly load amplitude. Two different load profiles, linear and nonlinear with respect to the number of cycles, were considered. The data were then analyzed by using a probabilistic failure model based on the Weakest-Link Theory and the classical stress-life function, before being transformed to simulate clinical data of direct restorations. Results: All the experimental data could be well fitted with a 2-parameter Weibull function. However, a calibration was required for the effective stress amplitude to account for the difference between static and cyclic loading. Good agreement was then obtained between theory and experiments for both load profiles. The in vitro model also successfully simulated the clinical data. Significance: The method presented will allow tooth-composite interfacial fatigue parameters to be determined more efficiently. With suitable calibration, the in vitro model can also be used to assess composite systems in a more clinically relevant manner.